Deformation and failure processes of glass-microballoon epoxy syntactic foam - Naidu, Aravin Dass (2013)
In this study, the response of Glass Micro-balloon Epoxy Syntactic Foam to compressive loading was experimentally investigated under high strain-rate conditions. The stress-strain response and deformation/damage history was used in the determination of relevant mechanical properties (Peak Stress, Peak Strain, Plateau Stress and Densification Strain) of Epoxy Syntactic Foam and in the development of a model to optimize the properties (fracture resistance and energy dissipation capacity) of such Polymeric Foams. To investigate the implications of micro-balloon wall thickness, micro-balloon outer radius, micro-balloon volume fraction, matrix variant and strain-rate, Glass Micro-balloon Epoxy Syntactic Foams were fabricated from a selection of glass spheres (S15, S22, S32, S38, K1 and K46), Epoxy matrices (Epicote 1006 and Epicote 1006A) and with varying volume fractions (0.1, 0.2, 0.3, 0.4). A pulse shaped Split Hopkinson’s Pressure Bar Test (SHPB) modified for low impedance material testing was used to ensure that the samples deformed under dynamic equilibrium and at a constant strain-rate. High Speed Camera imaging of samples undergoing failure and Scanning Electron Microscopy (SEM) were conducted to observe the micro-structural and macro-structural changes in Syntactic Foam during material failure. The results of SHPB testing revealed that when contrasted to quasi-static compression, Syntactic Foam subjected to high strain-rate loading possessed improved fracture resistance and energy dissipation capacity. Such behaviour was attributed to the failure of Syntactic Foam under dynamic conditions occurring indiscriminately through glass spheres and Epoxy matrix instead of crack propagation along preferred paths. Compressive strength and energy dissipation capacity was seen to decrease with increasing volume fraction. By studying the images captured in SEM, higher volume fractions samples were observed to have lower density and thus, resistance to failure. Incorporating a matrix of higher strength and improved fracture resistance was shown to enhance the mechanical properties of Polymeric Foams. Through the study of micro-structural changes during Syntactic Foam failure, it was determined that increased wall thickness improved the resistance to crack propagation thus, improving the mechanical properties of Foam. Increased outer radius was shown to weaken the sample. In combining both wall thickness and outer radius into a T/D (thickness/diameter) ratio, the fracture resistance and energy dissipation capacity of foam was seen to increase with T/D. It is suggested however at low T/D ratios energy dissipation capacity is high whereas at high T/D ratios fracture resistance is maximized. It was concluded that the optimal Syntactic Foam properties are achieved by increasing T/D ratio, decreasing volume fraction of glass spheres, incorporating a stronger matrix and loading under high strain-rate conditions.